Faktor-Faktor yang Memengaruhi Pemilihan Moda Transportasi Berjalan Kaki dan Sepeda di Kota Bogor - Aji Wibowo, Widianto; Herwangi, Yori (Jurnal Indonesia Sosial Sains, 2022)
The development of the city as an economic and trade node is very important for the urban system and the regional economy. The distribution of centralized public facilities and services attracts people to work in the city center. In these conditions, the ideal form of the city is needed because to reach work, school, public services and so on can be done only by walking or cycling. This study aims to examine the characteristics and behavior of walking and bicycle mode selection based on the shape of the urban environment, demographic, social and economic conditions of the community. And look at the factors that might influence the decision to choose the mode of transportation. This study uses a quantitative deductive approach. This research method is based on a questionnaire along with interviews and field observations. The study was conducted in eight urban villages in the city of Bogor. The target respondents are individuals who reside/domicile in the area. The results showed that walking mode was the most frequently chosen mode of travel. In addition, the bicycle mode is the second most frequently used mode. The influencing city form factor is the access and affordability of public facilities and services such as bus stops and commercial areas. In addition, population density and the level of land use are also influential factors. Furthermore, demographic, social, and economic factors that influence are income, personal vehicle ownership, days of travel, and ability to walk based on the furthest distance. In addition, there are other factors that influence, namely the travel time to the destination, affordable costs, as well as the safety and comfort of pedestrian and bicycle paths.